Limassol Cinema Club - (:unkn) unknown (My University, 2026)
The Limassol Cinema Club is a cultural association for the promotion of cinematic art in Cyprus, the acquaintance of the public with the work of important creators and the achievements of important national cinemas, the constant information about the new trends and searches of contemporary remarkable directors, the general spread of cinematic education in our country.